If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 2)(5x + 2) = 144 Reorder the terms: (2 + 5x)(5x + 2) = 144 Reorder the terms: (2 + 5x)(2 + 5x) = 144 Multiply (2 + 5x) * (2 + 5x) (2(2 + 5x) + 5x * (2 + 5x)) = 144 ((2 * 2 + 5x * 2) + 5x * (2 + 5x)) = 144 ((4 + 10x) + 5x * (2 + 5x)) = 144 (4 + 10x + (2 * 5x + 5x * 5x)) = 144 (4 + 10x + (10x + 25x2)) = 144 Combine like terms: 10x + 10x = 20x (4 + 20x + 25x2) = 144 Solving 4 + 20x + 25x2 = 144 Solving for variable 'x'. Reorder the terms: 4 + -144 + 20x + 25x2 = 144 + -144 Combine like terms: 4 + -144 = -140 -140 + 20x + 25x2 = 144 + -144 Combine like terms: 144 + -144 = 0 -140 + 20x + 25x2 = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(-28 + 4x + 5x2) = 0 Factor a trinomial. 5((-14 + -5x)(2 + -1x)) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-14 + -5x)' equal to zero and attempt to solve: Simplifying -14 + -5x = 0 Solving -14 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -5x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -5x = 0 + 14 -5x = 0 + 14 Combine like terms: 0 + 14 = 14 -5x = 14 Divide each side by '-5'. x = -2.8 Simplifying x = -2.8Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-2.8, 2}
| X-8=-4-26 | | 7x-3x-50=20 | | y-2(y-3)+4= | | 2x+3x-5=50 | | 35z-11=59 | | x=6(2x+1) | | -4-6=5x+9-4x | | 0(8b+4)= | | 26R-3R^2=0 | | 11x+3=2x | | -75=-3x+3 | | 4x-9-9-8x= | | 5j-j= | | X+X+10+2(2X+10)=180 | | 8h-4h= | | -9t+3=-10t | | 2x-(4y-3)+5+-3+-1= | | -(4xy-10)+3(3xy+6)= | | 6+4r=5r | | 3-3*6-2=12 | | 18-r=-323 | | -15x-14= | | 4x-1=10x+8 | | 22+z=-180 | | Y=x+-5 | | 249=4x^2+32x-11 | | 8-d=d-6 | | 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 | | 5t+7r-15r= | | 3t-8=-2t+7 |